2013
DOI: 10.1021/ic4023882
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Hydrogen Evolution from Water by a Series of Iron Carbonyl Clusters

Abstract: The development of efficient hydrogen evolving electrocatalysts that operate near neutral pH in aqueous solution remains of significant interest. A series of low-valent iron clusters have been investigated to provide insight into the structure-function relationships affecting their ability to promote formation of cluster-hydride intermediates and to promote electrocatalytic hydrogen evolution from water. Each of the metal carbonyl anions, [Fe4N(CO)12](-) (1(-)), [Fe4C(CO)12](2-) (2(2-)), [Fe5C(CO)15](2-) (3(2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 46 publications
1
77
1
Order By: Relevance
“…Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 . Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 .…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 . Berben et al [59][60][61] pioneered the synthesis of various iron carbonyl clusters (Figure 24) that facilitated the formation of CH bond, resulting in the production of formates from CO 2 .…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[6][7][8] To this end, the iron nitridocarbonyl cluster [Fe 4 (m 4 -N)(CO) 12 ] À was prepared over 30 years ago in an attempt to link this analogy to adsorbed nitrogen on iron surfaces in the Haber-Bosch process. [12][13][14] In contrast, the isoelectronic and isostructural species [Fe 4 (m 4 -C)(CO) 12 ] 2À is susceptible to protonation at the interstitial carbon atom and displays chemistry pertinent to the metal cluster-surface analogy,specifically carbon monoxide activation and the cleavage of H 2 across the m 4 -carbide. [9] Notably, the reactivity observed for [Fe 4 (m 4 -N)(CO) 12 ] À had been limited to monoprotonation and simple ligand exchange [11] until recently,w hen it was shown by Berben and co-workers that this species electrocatalytically reduces H + and CO 2 .…”
Section: Formanydecadesinvestigationsintotheprecisetrajectoriesmentioning
confidence: 99%
“…Molecular electrocatalysts play an important role in a wide range of energy conversion processes, including the oxidation and production of H 2 , the reduction of O 2 , N 2 and CO 2 , as well as the splitting of water into protons, electrons and O 2 . These considerations have led to the development of molecular catalysts employing more abundant metals, and several complexes that contain iron, nickel, iron, cobalt and molybdenum [7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been developed as electrocatalysts for the production of hydrogen. It has been shown that the donor type and the electronic properties of the ligands play vital roles in determining the structure and reactivity of the corresponding metal complexes.…”
Section: Introductionmentioning
confidence: 99%